Optimised Production Of Lovastatin Through Solid State Fermentation By Endophytic Fungi - RAGHUNATH R,; RADHAKRISHNA A,; MANIKANDAN N,; NATHIYA K,; PALANISWAMY M, (International Journal of Pharma and Bio Sciences, 2012)
Cardiovascular diseases, the main cause of death in the society imply a strong correlation between enhanced blood cholesterol levels. 3-Hydroxy-3-methylglutaryl–coenzyme A (HMG–CoA) reductase catalyzes the conversion of HMG–CoA to mevalonic acid, plays a significant role in cholesterol synthesis. Fungi are the important sources for the production of lovastatin, a rate limiting step of cholesterol biosynthesis. In this study, endophytic fungal strain Aspergillus niger was tested for its ability to produce lovastatin by solid-state fermentation (SSF). Various substrates were used to evaluate the ability of A. niger to produce lovastatin. The organism produced high levels (1.5 mg/g of dry substrate) of lovastatin under optimized culture conditions on 8th day of incubation at an optimum pH 6.5, temperature 28 °C, moisture content 65%, particle size of 0.6 to 0.4 mm and bed depth 3 cm by SSF. The yields obtained in the present study would have to be further increased for its industrial importance but it has proved the feasibility of solid state fermentation as a promising technique in exploiting cheaply available agro-residual wastes as substrates for the large-scale production of microbial metabolites of biotechnological importance ultimately leading to an effective solid waste management.